Program Keluarga Harapan and Senior Secondary Out-of-School Rates - Romadhoni, Ilham Irawan; Qibthiyyah, Riatu Mariatul (Faculty of Economic and Business Syarif Hidayatullah State Islamic University of Jakarta, 2024)
Research Originality: The novelty of this study lies in its use of a combined approach of probit analysis and propensity score matching to evaluate the impact of the Program Keluarga Harapan (PKH) on reducing out-of-school rates at the senior high school level, specifically before and after the COVID-19 pandemic.Research Objectives: The study aims to empirically assess the effectiveness of PKH in enhancing educational outcomes to break the cycle of poverty.Research Methods: The study also utilizes recent data from 2019 and 2022, reflecting the increased financial support of up to IDR 10 million per family per year. The analysis was conducted in two stages: first, on the overall sample of students from eastern Indonesia and other regions, and second, on a subsample of students in eastern Indonesia.Empirical Results: The results indicate that PKH was more effective in 2022, with a 2.3% reduction in the overall sample and a 1.4% reduction in the eastern Indonesian subsample in preventing students from dropping out of school compared to 2019.Implications: The study suggests that PKH can effectively support educational participation and reduce out-of-school rates, supplementing primary programs like PIP (Program Indonesia Pintar).JEL Classification: I26, I38